2010
DOI: 10.1007/s10551-010-0645-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Software Piracy in Jordan: An Extension of the Theory of Reasoned Action

Abstract: software piracy, Theory of Reasoned Action, religiosity, ethical ideology, public self-consciousness, low self-control, developing countries, Jordan,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 78 publications
6
81
0
2
Order By: Relevance
“…Attitude towards digital piracy is the key factor in influencing consumers’ intention to pirate digital product. This confirms previous empirical findings in several other developing countries, such as Barbados (Alleyne, Soleyn, & Harris, ), China (Chan & Lai, ; Chan et al, ; Wang et al, ; Yoon, ), Jordan (Aleassa et al, ), Indonesia (Arli et al, ; Casidy et al, ), Israel (Shoham, Ruvio, & Davidow, ) and Turkey (Akbulut, ). In terms of the determinants of consumer attitude towards digital piracy, deterrence theory seems to have a potential for the Indonesian context.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Attitude towards digital piracy is the key factor in influencing consumers’ intention to pirate digital product. This confirms previous empirical findings in several other developing countries, such as Barbados (Alleyne, Soleyn, & Harris, ), China (Chan & Lai, ; Chan et al, ; Wang et al, ; Yoon, ), Jordan (Aleassa et al, ), Indonesia (Arli et al, ; Casidy et al, ), Israel (Shoham, Ruvio, & Davidow, ) and Turkey (Akbulut, ). In terms of the determinants of consumer attitude towards digital piracy, deterrence theory seems to have a potential for the Indonesian context.…”
Section: Discussionsupporting
confidence: 89%
“…Consumers’ attitude towards digital piracy refers to an individual's favourable or unfavourable assessment regarding committing digital piracy. Previous empirical studies indicated that individuals who have a positive attitude towards digital piracy intend to pirate (Aleassa, Pearson, & McClurg, ; Arli, Tjiptono, & Porto, ; Casidy et al, ; Phau et al, ). Therefore, it is postulated that:
H1 Consumers’ attitude toward digital piracy will positively influence consumers’ intention to pirate digital products .
…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The theory has been applied and adapted to many types of voluntary behaviors, particularly consumer behaviors, including purchasing soft drinks, gasoline, toothpaste, banking, sports tickets, restaurants and food tourism (Bagozzi et al 2000;Kim et al, 2011;Ryan and Bonfield 1980;Sheppard et al 1988). More recently, the theory has been applied to online contexts, such as online stock trading (Ramayah et al 2009), software piracy (Aleassa et al 2011), cyberbullying (Doane et al 2014), sustainable purchasing contexts such as buying green products (Ramayah et al 2010), green information technology products (Mishra et al 2014) and purchasing green energy brands (Hartmann and Apaolaza-Ibanez 2012).…”
Section: Theory Backgroundmentioning
confidence: 99%
“…Generation Ys (those born between 1980-2000 1 ) are the first generation to have grown-up with the Internet which has made it easier for them to engage in unethical activities such as; online pornography, hate-sites, bomb/drug making websites, copyright violation (Hope 2006) and pirating software (Aleassa et al 2011;Liao, Lin and Liu 2010;Phau and Ng, 2010;Global Software Piracy Study, 2009, IFPI Digital Music Report 2010. This is partly because of the Internet's separate culture or "Netiquette" (Johnston and Johal 1999) which; enhances a false sense of reality, lowers potential levels of detection, lessens punishment for potential miscreants, allows the adoption of a virtual persona (Freestone and Mitchell 2004) and results in Internet risk perceptions being non-existent (Hope 2006).…”
Section: Introductionmentioning
confidence: 99%